2018
DOI: 10.1038/s41598-018-22850-4
|View full text |Cite
|
Sign up to set email alerts
|

Age-related Changes in Eye, Brain and Visuomotor Behavior in the DBA/2J Mouse Model of Chronic Glaucoma

Abstract: Although elevated intraocular pressure (IOP) and age are major risk factors for glaucoma, their effects on glaucoma pathogenesis remain unclear. This study examined the onset and progression of glaucomatous changes to ocular anatomy and physiology, structural and physiological brain integrity, and visuomotor behavior in the DBA/2J mice via non-invasive tonometry, multi-parametric magnetic resonance imaging (MRI) and optokinetic assessments from 5 to 12 months of age. Using T2-weighted MRI, diffusion tensor MRI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 85 publications
0
19
0
Order By: Relevance
“…These conditions are believed to be mainly induced by exposure to environmental conditions (Smith et al, 1994). The C57BL/6J strain is also widely used as a control strain for DBA/2J mice (Wong and Brown, 2007;Yang et al, 2018). Not surprisingly, in neither of these strains did we observe a sudden increase in IOP between the third and sixth months of life.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…These conditions are believed to be mainly induced by exposure to environmental conditions (Smith et al, 1994). The C57BL/6J strain is also widely used as a control strain for DBA/2J mice (Wong and Brown, 2007;Yang et al, 2018). Not surprisingly, in neither of these strains did we observe a sudden increase in IOP between the third and sixth months of life.…”
Section: Discussionmentioning
confidence: 77%
“…At this stage of pathology, retinal degeneration was already visible as optic disc cupping visible in T2w images and optic disc cupping was not visible in either of the control strains. Additionally, other groups reported various hallmarks of degeneration at this stage, including decrease of visuomotor function, alterations within the optic nerve, and the optic tract demonstrated by diffusion-weighted MRI (Yang et al, 2018).…”
Section: Discussionmentioning
confidence: 92%
“…The DBA/2J mouse model is a late onset, hereditary glaucoma model associated with age dependent increase in intraocular pressure. MEMRI studies with DBA/2J mice showed changes in ocular anatomy due to glaucoma (Calkins et al, 2008) and decreased manganese enhancement in superior colliculus, ON and lateral geniculate nucleus compared to control mice that was further decreased with age (Fiedorowicz et al, 2018; Yang et al, 2018). Similar results were obtained in an induced ocular hypertension rat model of chronic glaucoma, where decreased Mn 2+ enhancement in the ON of the glaucomatous eye was observed after intravitreal injection (Chan et al, 2008).…”
Section: Memri In Diseases With Neurodegenerative Componentsmentioning
confidence: 99%
“…Retinal Mn 2+ uptake decreases with age in old DBA/2J mice, and loss of axonal transport occurs before changes in retinal thickness (130). The visual pathway showed a significant reduction in Mn 2+ enhancement at 9 months and little enhancement by 12 months in DBA/2J mice (131), and early axonal transport may be impaired before elevated intraocular pressure develops (132). These MEMRI findings help us understand the pathogenesis of glaucoma and monitor the effects of drug interventions and provide an in vivo global perspective for investigations of the primary visual conduction system in rats.…”
Section: Glaucomamentioning
confidence: 93%